Empathy and ethical sensitivity among intensive and critical care nurses: A path analysis - Sharifnia, Amir Masoud (Nursing ethics, 2024)
BackgroundIntensive and critical care nurses need to demonstrate ethical sensitivity especially in recognizing and dealing with ethical dilemmas particularly as they often care for patients living with life-threatening conditions. Theories suggest that there is a convergence between nurses’ empathy and ethical sensitivity. Evidence in the literature indicates that nurses’ emotional, demographic, and work characteristics are associated with their level of empathy and ethical sensitivity.AimTo investigate the relationship between nurses’ empathy and ethical sensitivity, considering their emotional states (depression, anxiety, and stress), demographic and work characteristics, and test an empirical model describing potential predictors of empathy (as a mediator) and ethical sensitivity using path analysis.Research designUsing a cross-sectional design, the philosophical theory of care ethics and empathy was extended and adopted as a conceptual framework for this study and tested by path analysis.Participants and research contextData were collected from 347 intensive care nurses recruited by ten educational-medical hospitals in Iran using a questionnaire between February and March 2021.Ethical considerationsThe study was reviewed by the Ethical Advisory Board in Iran and conducted according to the Declaration of Helsinki.FindingsStudy participants demonstrated a mild level of stress, anxiety, and depression, alongside a relatively high level of empathy and ethical sensitivity. Nurses with good socioeconomic status had higher empathetic behavior with patients than those with weak status. Nurses aged over 40 who had received ethics training and had higher work experience were associated with higher ethical sensitivity compared to nurses under 20 years of age. Empathy directly affected ethical sensitivity; however, anxiety had an indirect effect on ethical sensitivity through empathy. Among demographic factors, age had a positive direct effect on ethical sensitivity.ConclusionsLess anxiety and a high level of empathy contribute to higher levels of ethical sensitivity among intensive and critical care nurses.